The role of the dihydroxyacetone phosphate acyltransferase LmDAT in lipophosphoglycan synthesis, metacyclogenesis and autophagy in Leishmania major - Al-Ani, Gada K. Khalil (Kansas State University, 2007)
Glycerolipids are the most abundant lipids and are important constituents of various virulence factors in the protozoan parasite Leishmania. The dihydroxyacetone phosphate acyltransferase LmDAT catalyzes the first step of the ether, and possibly ester glycerolipid biosynthetic pathway. A L. major null mutant of LmDAT grew slowly, died rapidly during the stationary phase of growth, and more importantly, was attenuated in virulence in mice. The goal of this study was to determine the molecular basis responsible for the attenuated virulence. Western blot analysis revealed that the ∆lmdat/∆lmdat null mutant synthesized altered versions of the virulence factor lipophosphoglycans that were not released in the media, suggesting that its lipid anchor structure was altered. The ∆lmdat/∆lmdat strain differentiated into virulent metacyclics, but with lower efficiency compared to the wild type. Using the autophagosomal marker ATG8-GFP, the ∆lmdat/∆lmdat line produced twice as many autophagosomes as the wild type, suggesting that it is either defective in degradation of autophagosomes or that autophagy is simply induced. In conclusion, the attenuated virulence of ∆lmdat/∆lmdat may be explained by i) its inability to synthesize and release normal forms of lipophosphoglycan, ii) its inability to fully differentiate into virulent metacyclics, and iii) altered autophagy.
Keywords: Leishmania major; Lipophosphoglycans; Dihydroxyacetone phosphate acyltransferase; Metacyclogenesis; Autophagy; Biology, Microbiology (0410); Biology, Molecular (0307)